O Cadastro Territorial Multifinalitário como instrumento na Gestão do Território - Rúbio, Mônica Rodrigues Brisolla (2011)
The present work points out the importance of developing studies in order to contribute and offer territory management tools which may organize data and subsidize urban planning. These tools are supposed to improve life in the city as well as resolving or minimizing its problems. Legal instrumentation is complex and, through the urban legislation available to Brazilian cities nowadays, allows for many instruments of regulation and city management. Such instruments account for minimization and problem control as well as complying with the social function of urban property. Issues concerning organization, resources and technical training are some of the various obstacles to the effect usage of this legal framework in the City Halls. Territorial Cadastres are precarious and deficient. Hence, they must be outlined and developed so as to accomplish their fiscal role and expand this role as an important instrument of territory management. Therefore, the present work introduces a method of designing Territorial Cadastre methodology derived out of Urban Cartography, which is available to Municipalities in Parana in digital form. Such methodology may subsidize the territory management process in City Halls